Transnational Higher Education Strategies into and out of Singapore: Commodification and Consecration. Issue 1 (24th November 2015) - Ye, Rebecca
Abstract: This article addresses transnational higher education strategies both to and from Singapore. It does so by focusing on outbound educational mobility from Singapore to the UK and inbound educational mobility from Vietnam to Singapore. Since the turn of the century, Singapore has pursued the agenda of developing itself as a regional hub for higher education, aspiring to be a Global Schoolhouse. Yet, while the number of international students grows in local universities, Singapore's academically brightest do not necessarily take advantage of higher educational opportunities within the shores of the city-state, with many traveling to universities overseas through a form of sponsored mobility. Using two case studies, I trace two logics of commodification and consecration as observed through the processes whereby individuals and institutions devise transnational higher education strategies into and out of Singapore. The first case study draws on interviews conducted with Singaporean undergraduates at Oxbridge while the second case focuses on Vietnamese students at two Singaporean universities. Together, the analysis from these cases uncovers the value for these Southeast Asian students in studying abroad and distinguishes between different types of routes that exist: one where students choose their own educational plans and another where students are chosen for a prestigious educational and occupational pathway. With increasing participation in mass higher education taking place across the region, the article outlines, through the site of Singapore, strategies of transnationalism employed by both individuals and institutions as a means of social differentiation.